2016
DOI: 10.1089/neu.2015.4183
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study Exploring Factors Associated with Provider Adherence to Severe Pediatric Traumatic Brain Injury Guidelines

Abstract: Despite demonstrated improvement in patient outcomes with use of the Pediatric Traumatic Brain Injury (TBI) Guidelines (Guidelines), there are differential rates of adherence. Provider perspectives on barriers and facilitators to adherence have not been elucidated. This study aimed to identify and explore in depth the provider perspective on factors associated with adherence to the Guidelines using 19 focus groups with nurses and physicians who provided acute management for pediatric patients with TBI at five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 48 publications
5
27
0
Order By: Relevance
“…Effective implementation strategies can amplify the crucial work done in basic and translational research by closing the gap between knowledge and practice, increasing the impact of on patient survival and outcomes. A rigorous scientific approach to the development and testing of implementation strategies will be required, and barriers such as guideline credibility and applicability to individual patients, provider culture, communication style and attitudes towards care protocols will have to be addressed (34). As translational and clinical research continue to generate knowledge and strengthen clinical evidence, effective implementation science strategies will facilitate the application of precision medicine to neurocritical care, allowing care providers to identify, select and schedule therapies that are most likely to yield a favorable outcome for and individual patient (35).…”
Section: Resultsmentioning
confidence: 99%
“…Effective implementation strategies can amplify the crucial work done in basic and translational research by closing the gap between knowledge and practice, increasing the impact of on patient survival and outcomes. A rigorous scientific approach to the development and testing of implementation strategies will be required, and barriers such as guideline credibility and applicability to individual patients, provider culture, communication style and attitudes towards care protocols will have to be addressed (34). As translational and clinical research continue to generate knowledge and strengthen clinical evidence, effective implementation science strategies will facilitate the application of precision medicine to neurocritical care, allowing care providers to identify, select and schedule therapies that are most likely to yield a favorable outcome for and individual patient (35).…”
Section: Resultsmentioning
confidence: 99%
“…The decision to place an ICP monitor in the ED may also depend on physician preference or practice, as well as on organizational culture around placement of other advanced monitoring techniques relevant to severe TBI care. As we relied on existing data, we were unable to study whether physician level factors [30] were associated with ED ICP monitor placement. Finally, because we excluded patients who died within the first 48 hours of admission to trauma center in the parent PEGASUS study, select factors in our study may not have shown significant associations with ED ICP monitor placement.…”
Section: Limitationsmentioning
confidence: 99%
“…1 2 Factors associated with clinician non-adherence to TBI guidelines were: 1) concern about guideline credibility and applicability to patient care, 2) lack of implementation, dissemination, and enforcement strategies, and 3) provider culture, communication style, and attitudes towards protocols. 3 The global objective of this project was to reduce variability among care provided to children with severe TBI by developing and implementing a standard clinical care TBI pathway to promote adherence to the evidence-based TBI Guidelines.…”
Section: Problemmentioning
confidence: 99%